RELIABILITY OF SCADA SYSTEMS IN BiH SUBSTATIONS - Savic, Goran; Tadić, Goran (Journal of Engineering & Processing Management, 2022)
This paper describes the concept of modern SCADA systems in general, as well as in BiH substations, and its connection to remote control centers, with a focus on redundancy, reliability and availability. Also, benefits from the usage of redundant protocols, RTU redundancy, usage of industrial equipment designed to work in substation environment and parameters needed for these systems are discussed in this paper. Besides local SCADA systems, telecommunication issues regarding connection to remote control centers are also considered.